PREPARATION and CHARACTERIZATION of CELLULOSE/HYDROUS NIOBIUM PHOSPHATE HYBRID - Fernandes Pereira, Paulo H. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila H. [UNESP]; Caetano Pinto da Silva, Maria Lucia (North Carolina State Univ Dept Wood & Paper Sci, 2010)
In recent years, increasing attention has been directed to the use of renewable resources, particularly of sugarcane bagasse. Considering the abundant availability of such lignocellulosic materials, relatively few attempts have been made regarding their utilization. Studies about properties and morphology, heavy metal adsorption, and membranes preparation have been conduced by this research group in order to use these materials. In this paper, cellulose fibers obtained from sugarcane bagasse were bleached and modified by hydrous niobium phosphate. Hybrids (cellulose/NbOPO(4)center dot nH(2)O) were prepared from metallic niobium dissolved in a fluoridric/nitric (10:1) mixture, to which cellulose sugarcane bagasse was added. Afterwards a concentrated orthophosphoric acid (85mL, 85% w/w) was added to precipitate hydrous niobium phosphate particles. This material was characterized by X-ray diffraction (XRD), thermogravimetry (TG/DTG), and differential scanning calorimetry (DSC) analyses, as well as scanning electronic microscopy (SEM) coupled to an energy dispersive spectrophotometer (EDS). Morphological studies of bleached cellulose revealed different sizes and arrangement of cells, showing that NbOPO(4)center dot nH(2)O was present in the cellulose structure. Thermal stability of the hybrid was observed up to approximately 200 degrees C, and the cellulose decomposed at 300 degrees C. These data will help finding new uses for these materials.
Keywords: Cellulose; Hydrous niobium phosphate; Sugarcane bagasse